INTERACTIVE CONTEXTUAL MULTIMEDIA EFFECTS ON EARLY READING SKILLS AMONG SLOW-LEARNER-RISK ELEMENTARY STUDENTS - Reni Anjarwati; Bayu Pamungkas (PT Altin Riset Publishing, 2026)
This study aims to analyze the effect of using contextual interactive multimedia on the beginning reading skills of third-grade elementary school students at risk of being slow learners. The study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The participants were four students identified as having difficulties in beginning reading based on an initial assessment. Reading skills were assessed across five indicators: letter recognition, syllable decoding, word-reading accuracy, reading fluency, and comprehension of simple texts. The data were analyzed using descriptive statistics, gain scores, the Wilcoxon signed-rank test, and effect size estimation. The findings showed improvements in reading performance among all participants following the intervention. The mean score increased from 51.25 at the pretest to 73.75 at the posttest, representing a mean improvement of 22.50 points, with all participants achieving positive gain scores. These findings indicate that contextual interactive multimedia has the potential to support the development of beginning reading skills through the integration of visual and auditory representations, contextual learning experiences, teacher scaffolding, and feedback. However, the findings should be interpreted cautiously because of the very small sample size and the absence of a control group. Further research involving larger samples and stronger experimental designs is needed to examine the effectiveness and generalizability of the intervention.